A t(6;14;9)(p22;q22;q34) three‐way translocation: Description of a cytogenetically visible variant t(6;9) in acute myeloid leukemia. Issue 7 (24th March 2022) - Smith, Adam C.; Maze, Dawn; Xia, Daniel; Capo‐Chichi, Jose‐Mario; King, Ian; Sibai, Hassan
Abstract :